2020
DOI: 10.1021/acs.inorgchem.0c01266
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular Holes in Porphyrin Isomers Act As Mono- and Binucleating Ligands: Stereochemistry of Mono- and Diboron Porphycenes and Their Protonation Behaviors

Abstract: The first boron complexes of porphycenes, structural isomers of porphyrin, are reported. They are synthesized in good yields by reacting the free-base porphycene ligands with BF3·Et2O through a microwave-assisted method. Depending on the substituent group of porphycenes, two different coordination structures, mono- and diboron porphycenes, are obtained simultaneously. The single crystal structures and DFT calculations suggest that the boron atom of the monoboron porphycene is favorably coordinated on the dipyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The structures of these dyes were determined with exceptional accuracy and reliability through the use of multiple nuclear magnetic resonance (NMR), highresolution mass spectrometry (HRMS), and X-ray crystal analysis. The presence of two sets of triplet boron signals in 11 B NMR spectra and two sets of quadruplet fluorine coupling signals in 19 F NMR spectra further confirms the structures of the bisBF 2 -anchoring BOPPY dyes. X-ray Crystal Diffraction.…”
Section: ■ Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…The structures of these dyes were determined with exceptional accuracy and reliability through the use of multiple nuclear magnetic resonance (NMR), highresolution mass spectrometry (HRMS), and X-ray crystal analysis. The presence of two sets of triplet boron signals in 11 B NMR spectra and two sets of quadruplet fluorine coupling signals in 19 F NMR spectra further confirms the structures of the bisBF 2 -anchoring BOPPY dyes. X-ray Crystal Diffraction.…”
Section: ■ Introductionsupporting
confidence: 58%
“…All reactions were performed in oven-dried or flame-dried glassware unless otherwise stated and were monitored by TLC using 0.25 mm silica gel plates with a UV indicator. 1 H, 11 B, 19 F, and 13 C NMR were recorded on a 300 or 400 MHz NMR spectrometer at room temperature. Chemical shifts (δ) are given in ppm relative to internal TMS (0 ppm), CDCl 3 (7.26 ppm for 1 H NMR and 77.16 ppm for 13 C NMR).…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugated organoboron complexes containing N–B–N, O–B–O, or N–B–O bridges with five-, six-, and seven-membered core rings have played important roles in both fundamental studies and light-guiding applications, such as noninvasive bioimaging, molecular sensing, optoelectronic devices, and information display. In particular, tetracoordinate boron­(III) compounds with bidentate chelating ligands have been in the focus of these efforts owing to their rich and unique properties. The boron complexation increased rigidity of target compounds and was often accompanied by significantly increased chemical stability and photostability and high fluorescence quantum yields.…”
Section: Introductionmentioning
confidence: 99%
“…25 Hisaeda and co-workers, in 2021, reported the first ever boron complexes of porphycenes (Figure 1). 27 A microwave-assisted reaction of meso-substituted porphycenes with BF 3 •OEt 2 and Et 3 N in chlorobenzene as the solvent resulted in a mixture of mono-BF 2 and B−O−B complexes in the case of phenyl and 3,5-difluorophenyl as substituents and only the B−O−B complex in the case of 3,5-di-(trifluoromethyl)phenyl as the substituent. DFT calculations suggested that the cisoid arrangement of the B−O−B complex was more stable than the transoid one.…”
Section: ■ Introductionmentioning
confidence: 99%